Diagnosis of merchandising of the trading company "Calzafino" - Hidalgo Pumagualle, Esteban; Villacres Pumagualle, María; Zabala Jarrín, Harold Alexi; Palmay Jiménez, Anabel Fernanda (mktDESCUBRE, 2021)
The research addresses the merchandising diagnosis of the Calzafino trading company, in order to identify the current state of the point of sale and propose improvements for the management of visual merchandising, management, seduction, for the shopper customer and buyer client of the company. The study included 191 people belonging to the urban parishes Lizarzaburu and Veloz of the city of Riobamba, as well as the manager of Calzafino. The methodology used was a field study and documentary research, which was based on the application of a merchandising questionnaire to the current clients of the company, the adaptation of the RMG matrix for the menchandising audit carried out to the manager and finally the merchandising observation sheet according to their nature and types of customers. The results showed that Calzafino has the following weak points: the color of the establishment is not in accordance with the line of business, its lighting is low, advertising inside and outside the premises is deficient, it does not have a correct location of prices, decoration and signage of the establishment is not appealing to its current customers.